Implementing public policy an introduction to the study of operational governance - Hill, Michael J. (Michael James) 1937-; Hupe, Peter (SAGE, 2022)
The only book to focus on implementing public policy, this state-of-the-art text offers a comprehensive and lively account of the major insights found in implementation theory and research. Its exploration of the field provides a reflective overview of work in the study of policy implementation worldwide. In doing so, the book reconceptualizes the policy process to highlight the essential role those implementing policy have in moulding, shaping and directing policy during their work. Realizing policy goals may be the key to ballot box victory, while policies perceived as failures may symbolise declining trust and confidence in government and politics. As such, implementing policy is as crucial to the actors in power as it is for democracy. Policymakers respond to challenging problems in highly dynamic and pressurised contexts. From the global pandemic to climate change, financial regulation to education, effective policy has never been more important to governments and society - and the role of street-level bureaucrats in implementing policy never so crucial. This is the seminal work in the field, used by thousands worldwide. Now fully revised and updated, the 20th anniversary edition includes substantial changes and additions. This edition features two entirely new chapters on the consequences of populism and the latest street-level bureaucracy research, as well as extensive examination of comparative cross-national work and a refined and more explicit conceptualization of implementation in terms of its role in governance throughout. The book concludes with an all-new chapter exploring emergent issues on implementation in practice and on the research agenda. --